Iodine status of pregnant women living in urban Johannesburg, South Africa. Issue 1 (30th June 2021) - Siro, Sicelosethu S.; Zandberg, Lizelle; Ngounda, Jennifer; Wise, Amy; Symington, Elizabeth A.; Malan, Linda; Smuts, Cornelius M.; Baumgartner, Jeannine
Abstract: Adequate intake of iodine is important during pregnancy because of its essential role in foetal growth and neurodevelopment. Data on iodine status of South African pregnant women are scarce, and the salt reduction policy implemented in 2016 may decrease iodine intake of South Africans. This cross‐sectional study assessed the iodine status of pregnant women residing in urban Johannesburg, South Africa. A total of 250 pregnant women were enrolled into the 'Nutrition during Pregnancy and Early Development' (NuPED) study and 312 pregnant women into the 'Assessment of dried blood spot thyroglobulin in pregnant women to redefine the range of median urinary iodine concentration that indicates adequate iodine intake, South Africa' (STRIPE‐SA) study and were included in this analysis. Urinary iodine concentration (UIC) was analysed in a spot urine sample. Thyroglobulin (Tg) was measured in serum, and thyroid‐stimulating hormone (TSH) and total thyroxine (tT4) were measured in dried blood spots. The median [interquartile range (IQR)] UIC of pregnant women was 144 (84–234) μg/L. Women in the first ( n = 99), second ( n = 262) and third ( n = 174) trimester had a median UIC of 133 (81–316), 145 (84–236) and 156 (89–245) μg/L, respectively ( p = 0.419). Median TSH, tT4 and Tg were 2.7 (2.3–3.2) mU/L, 202 (163–236) nmol/L and 9.2 (5.4–17.9) μg/L, respectively. Based on the median UIC, pregnant women residing in urban Johannesburg may be borderline iodine deficient. These findings highlight the need for ongoing monitoring of iodine status among vulnerable pregnant women, especially considering the recently introduced salt reduction policy in South Africa.